Production of dispersions with small particle size from commercial indium tin oxide powder for the deposition of highly conductive and transparent films - Mahajeri, Mahdi; Schneider, Andreas; Baum, Marcus; Rechtenwald, T.; Voigt, Michael; Schmidt, Michael; Peukert, Wolfgang (Thin Solid Films, 2012)
Indium tin oxide (ITO) nanoparticle films for applications in printable electronics were prepared by dip-coating. The dispersion conditions (bead size, stabilizer concentration) strongly affect the particle size of the ITO suspensions and consequently determine the surface morphology of the ITO films. Deposition from ethanolic ITO suspensions with an extremely small particle size of 17 nm to 21 nm led to the formation of extremely smooth and spike-free ITO films with a typical root mean square surface roughness of 4.5 nm +/- 0.2 nm and a high optical transparency above 95%. The effect of annealing with forming gas and CO2 laser treatment on the electrical properties of the ITO films was investigated. Annealing with forming gas and CO2 laser treatment led to a temporary increase in the electrical conductivity of the ITO films by up to a factor of 10 and 6, respectively. Specific conductivities of up to 196 S cm(-1) were obtained for our ITO nanoparticle films under optimized conditions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Indium tin oxide; Nanoparticles; Suspension; Conductivity; Laser treatment; Forming gas treatment